Blockholders and firm performance: a Malaysian evidence - Mokhtar, Imani; Syed Mohd Zain, Sharifah Raihan; Duasa, Jarita; Mohamad, Azhar (Academic Research Publishing Group, 2018)
This study enhances the corporate governance literature by investigating the influence of blockholders on firm performance. Employing panel data estimations, this study works on a sample of 526 non-financial listed firms in Malaysia from 2006 to 2015. Overall, our findings reveal that firm performance is negatively associated with blockholders presence but positively related to blockholders total ownership concentration. Further examinations reveal that identity of blockholders matters in influencing performance of the firm. We also found that board governance mechanisms particularly independent directors and CEO duality play a significant monitoring role in relation to firm performance. More importantly, our findings are robust to a wide variety of performance measure which includes accounting, market and value based measures. Finally, findings of our study could facilitate the regulatory bodies and firm managers in promoting better and effective corporate governance in Malaysia. Investors may also benefit from our findings in understanding corporate governance of Malaysian firms and thus diversify their investment portfolios.